2000
DOI: 10.1243/0954407001527574
|View full text |Cite
|
Sign up to set email alerts
|

The dimensional quality of sheet metal assembly with welding-induced internal stress

Abstract: The present paper is the first to propose a minimum stress criterion for the minimum dimensional variation during sheet metal assembly. The weld sequence affects the dimensional variation owing to the welding process. A case study illustrates the minimum stress criterion on dimensional variation. This paper proposes a generic design criterion for sheet metal products and processes that would produce minimal stress-induced dimensional variation for spot-welded sheet metal assemblies. The process design proposes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Body assembly sheet metal dimension variations due to various welding sequences were studied and the author has recommended few design guide lines to the sheet metal designers to select the weld sequences to set appropriate Geometry. Design guide lines are provided to make stress free welding and stress relief patterns for different joineries (Shiu et al, 2000). The dimensional variation effects due to positional variation of spot weld was studied by Mali and Inamdar (2012) and he has concluded that, "spot weld position variation control is essential to maintain proper assembly dimensional accuracy".…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Body assembly sheet metal dimension variations due to various welding sequences were studied and the author has recommended few design guide lines to the sheet metal designers to select the weld sequences to set appropriate Geometry. Design guide lines are provided to make stress free welding and stress relief patterns for different joineries (Shiu et al, 2000). The dimensional variation effects due to positional variation of spot weld was studied by Mali and Inamdar (2012) and he has concluded that, "spot weld position variation control is essential to maintain proper assembly dimensional accuracy".…”
Section: Literature Reviewmentioning
confidence: 99%
“…There have been more than one research conducted in the past on the analysis of body assembly dimensional variations; and the two major focused areas are: 1 assembly processes 2 resistant spot welding process. Shiu et al (2000) stated that "the dimensional stability increases the productivity and reduces the quality related problems. Welding process failure and dimensional variation are some of the major factors for decrease in productivity".…”
Section: Introductionmentioning
confidence: 99%
“…There is some research done on optimization of spot welding sequences. Shiu et al [26] investigate the relationship between stress build-up due to different spot welding sequences and the resulting dimensional variation. General guidelines for welding sequences are also Figure 7.…”
Section: Joining Sequences In Variation Simulationmentioning
confidence: 99%
“…In the automotive industry, body assembly is a crucial operation to evaluate the overall quality of body-in-white, typically in improving gap evenness and flushness [43][44][45][46][47]. It is also very important to achieve acceptable gauge R&R results from these types of panels because of their non-rigidity [44,48].…”
Section: Casementioning
confidence: 99%